Perbandingan Algoritma Stout Code Dan Algoritma Elias Delta Code Dalam Kompresi File Video - Lili Rahmawati M. Yus (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
Data compression technology is the process of converting a set of data into a lower coded form of data representation that is not encoded with a certain encoding. Data compression is done by encoding each character into a shorter code message, with the aim of saving the need for storage space and time for data transmission. Compressor is used to speed up the process of sending from non-encoded characters to certain encoded characters. By compressing, large data will be reduced in size so that it can save storage capacity. In this study using the Stout Code Algorithm, by using this method the compression results are very good in transmitting data and transferring video file allocations more easily and quickly. By compressing, large data will be reduced in size so that it can save storage space. There are many types of methods or algorithms in video file compression, but in this algorithm the author only wants to know the compression process using the Stout Code and Elias Delta Code algorithms where the author has succeeded in compressing a video file with the Elias Delta Code algorithm, then the Elias Delta Code algorithm is the the best algorithm in the compression process.